The turbulent world of Franz Göll : an ordinary Berliner writes the twentieth century - Fritzsche, Peter 1959- (Harvard Univ. Press, 2011)
The case of Franz Göll, graphomaniac -- Franz's multiple selves -- Physical intimacies -- The amateur scientist -- Franz Göll writes German history -- Resolution without redemption